The Cost of Air Pollution : Strengthening the Economic Case for Action - World Bank; Institute for Health Metrics and Evaluation (World Bank, Washington, DC, 2016)
The Cost of Air Pollution: Strengthening the economic case for action, a joint study of the World Bank and the Institute for Health Metrics and Evaluation (IHME), seeks to estimate the costs of premature deaths related to air pollution, to strengthen the case for action and facilitate decision making in the context of scarce resources. An estimated 5.5 million lives were lost in 2013 to diseases associated with outdoor and household air pollution, causing human suffering and reducing economic development. Those deaths cost the global economy about US$225 billion in lost labor income in 2013 and more than US$5 trillion in welfare losses, pointing toward the economic burden of air pollution.